Bone augmentation by octacalcium phosphate and collagen composite coated with poly‐lactic acid cage - Toshiki Yanagisawa; Ayato Yasuda; Ria I. Makkonen; Shinji Kamakura (Wiley, 2020)
Abstract Objective Although octacalcium phosphate and collagen composite (OCP/Col) has demonstrated excellent bone regeneration, it has never achieved bone augmentation. The present study investigated whether it could be enabled by OCP/Col disks treated with parathyroid hormone (PTH) and covered with a poly‐lactic acid (PLA) cage. Materials and methods The prepared OCP/Col disks with three different types of PLA cages (no hole, one large hole, several small holes) were implanted into subperiosteal pockets in rodent calvaria. Histological, and histomorphometric analyses were conducted at 12 weeks after implantation. Results Implants with all PLA cage variants achieved sufficient bone augmentation, and analyses showed that new bone was formed from the original bone and along the PLA cage. While the PLA cage variant with no holes sporadically evoked new bone formation even at the central area of the roof of the PLA cage, the PLA cage variants with holes had no new bone in the area of the hole or beneath the periosteum. Conclusions These results suggest that sufficient bone augmentation could be achieved by treating the OCP/Col disks with PTH and covering them with a PLA cage, and periosteum might not have been involved in the bone formation in this experiment.